Half soccer season induced physical conditioning adaptations in elite youth players - Arregui-Martin, M. A.; Garcia-Tabar, I.; Gorostiaga, E. M. (International Journal of Sports Medicine, 2020)
This study aimed to investigate training-induced fitness changes and their relationship with training-competition load during half a soccer season (18 wks). Training load [heart rate (HR) and ratings of perceived exertion (RPE)] and match time were monitored, including 108 training (3223 individuals) and 23 match sessions, in 38 youth elite male soccer players. Fitness variables were assessed before and after the study. Yo-Yo intermittent recovery test 1 (Yo-Yo IRT1) improved (P<0.001; 90%CI: 418-632?m; ES: 2.14). Anthropometrical, jump, sprint, and change-of-direction measures remained unchanged. Jump test correlated with sprint (r=0.74; P<0.001; SEE=3.38?m·s-1) and Yo-Yo IRT1 (r=-0.58; P=0.005; SEE=4.11 m) tests. Initial sum of 6 skinfolds was associated with changes in this same measure (r=-0.51; P<0.001; SEE=21%). Initial Yo-Yo IRT1 results were related to changes in Yo-Yo IRT1 (r=-0.84; P<0.001; SEE=10%) and match time played (r=0.44; P=0.033; SEE=445 m). Mean RPE records were related to training spent within 75-90% maximal HR (r=0.54; P<0.001; SEE=4%). The half-season was beneficial for endurance running performance but not for lower-limb strength-velocity production capacity. The more aerobically deconditioned players played fewer minutes of match, although they showed the greatest improvements in endurance performance. Non-soccer-specific, scientifically based, and individualized fitness programs in addition to soccer-specific training are recommended.